Hybrid cylindrical dielectric resonator antenna with HE11δ and HE12δ mode excitation for wireless applications. Issue 9 (23rd August 2016) - Gangwar, Ravi Kumar; Sharma, Anand; Gupta, Mohit; Chaudhary, Shailja
Abstract: In this article, dual mode triple band hybrid cylindrical dielectric resonator antenna (CDRA) for different wireless applications is investigated. It is seen that annular ring shaped patch along with T‐shaped printed line behaves as a magnetic and electric dipole concurrently and create HE11δ and HE12δ mode in the proposed CDRA. Both of the hybrid modes radiate in broadside direction. The concept of hybrid antenna (the combination of annular ring patch and CDRA) is used to achieve triple‐band feature in the proposed antenna. Ansoft HFSS‐EM simulator is used to optimize the proposed antenna. Optimized simulated results have been practically confirmed by using the archetype of proposed antenna. The proposed radiator is applicable in three different frequency bands, that is, 2.24‐2.56 GHz, 3.28‐4.18 GHz, and 5.36‐5.8 GHz. It is appropriate for WLAN (2.4/5.8 GHz) and WiMAX (2.5/3.3/5.5 GHz) applications.